2001
DOI: 10.1177/00220345010800090901
|View full text |Cite
|
Sign up to set email alerts
|

Low Metacarpal Bone Density, Tooth Loss, and Periodontal Disease in Japanese Women

Abstract: The relationship between periodontitis and systemic bone mineral density in Japanese women is undetermined. We tested the hypothesis that periodontitis was more frequent in women with low metacarpal bone mineral density (m-BMD). Subjects were 190 Japanese women (89 premenopausal, 101 post-menopausal). Periodontal status was evaluated according to the Community Periodontal Index of Treatment Need (CPITN). M-BMD was measured by computed x-ray densitometry. The proportion of subjects with periodontitis (CPITN > o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0
12

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(84 citation statements)
references
References 19 publications
1
69
0
12
Order By: Relevance
“…The imbalances in bone remodelling associated with osteopaenic or osteoporotic conditions can thus lead to a net loss of bone density throughout the skeleton, including the oral cavity, possibly leading to tooth mobility. In post-menopausal women, osteoporosis-associated loss of crestal alveolar height (7)(8)(9) and increased frequency of crestal alveolar bone density loss have been reported (10). These findings may be attributed to increased local production of active alveolar bone cytokines interleukin (IL)-1β and IL-6 (11).…”
Section: Introductionmentioning
confidence: 99%
“…The imbalances in bone remodelling associated with osteopaenic or osteoporotic conditions can thus lead to a net loss of bone density throughout the skeleton, including the oral cavity, possibly leading to tooth mobility. In post-menopausal women, osteoporosis-associated loss of crestal alveolar height (7)(8)(9) and increased frequency of crestal alveolar bone density loss have been reported (10). These findings may be attributed to increased local production of active alveolar bone cytokines interleukin (IL)-1β and IL-6 (11).…”
Section: Introductionmentioning
confidence: 99%
“…Papers addressing the relationships among osteoporosis, estrogen deficiency and periodontitis have been published [2,3,6,[20][21][22][23]. It has been suggested that estrogen deficiency may be a risk factor for tooth loss [3,13,24,25], might affect dental implant success or compromise osseous support in totally edentulous subjects, leading to difficulty in wearing dentures. However the contribution of osteoporosis to tooth loss is difficult to demonstrate because teeth can be lost for several reasons other than the loss of bone support [26].…”
Section: Discussionmentioning
confidence: 99%
“…Entre los trastornos sistémicos crónicos de carácter músculo-esquelético y que se asocian a alteraciones orales, se encuentran la osteopenia y la osteoporosis, la artritis reumatoide, el lupus eritematoso y la enfermedad de Paget [32,[36][37][38], trastornos que se encuentran asociados como un factor de riesgo que produce pérdida del soporte óseo a nivel de las estructuras dentales [1,20,21].…”
Section: Calidad De Vida Y Salud Oralunclassified